Penerapan Model Pembelajaran Kooperatif Tipe Snowball Throwing Pada Muatan Pelajaran IPS di Kelas V SD - nasaruddin nasaruddin (Universitas Negeri Makassar, 2020)
The purpose of this research is to improve social studies learning outcomes in fifth grade elementary school by applying the snowball throwing type of cooperative learning model. The approach used is a descriptive qualitative approach, the type of CAR (Classroom Action Research). The results of data analysis showed that learning using the Snowball Throwing Cooperative Learning Model from cycle 1 to cycle II showed an increase where in cycle I learning completeness was 45% of 20 students while in cycle II learning completeness had reached 90%. So it can be concluded that by using the Snowball Throwing Cooperative Learning Model, it can improve the social studies results of fifth grade students at SD Inpres 77 Manurung, Bone Regency